Aprendizagem escolar e busca pelo direito à igualdade de resultados: um estudo sobre grupos interativos no ensino fundamental - Assis, Janaina Silva de (2019)
Diversity, heterogeneity, interaction, dialogue, and better results are some of the elements of the Interactive Group proposal, one of the successful educational activities developed in Learning Communities, which has as one of its objectives to reinforce and accelerate learning. contemplating the diversity of students who make up a classroom Given this dimension, this dissertation starts from the following question: What are the contributions and limitations of Interactive Groups for improving school learning and greater equality in learning outcomes among elementary school children? Outlining the following objectives: a) to identify, describe and analyze the contributions and limits of the Interactive Group to improve the school learning of students from an elementary school class in Goiânia and b) to identify, describe and analyze the contributions and limits Interactive Groups for the equality of results among the students, considering the learning of school contents. As a theoretical basis, it uses references from different scientific areas, which underlie the concept of dialogic learning, deepening in the concepts of Interaction and Mediation by the author Lev Semionovich Vigotski and in the conception of dialogue of the author Paulo Freire. It is inspired by the Communicative Methodology from a qualitative approach, configuring itself in a case study with an elementary school class in one of the municipal public schools of the city of Goiânia / Goiás, involving techniques of data collection of the Communicative Methodology. as Communicative Observations, Communicative Life Report, and Focus Group. This paper will present the text prepared for the defense of this dissertation, which is organized in three sections beyond the introduction and the final considerations. Presenting as results the analysis of subjective and objective data on the contributions of Interactive Groups to improve learning of school content in the early years of elementary school, ascertaining with the analysis of subjective data, transforming elements, exclusion and recommendation of speech of subjects. ascertaining the GI as an action that promotes the learning potential of the instrumental dimension. Besides improving the coexistence between the subjects, it provides the motivation, raising the interest of the students to continue learning more. Through the objective data it is possible to verify that the GI is contributive and motivating to the instrumental learning, because the school content gains a different aspect, is deeply worked, each theme / activity is performed by all collaboratively and in a more agile time, promoted through mediation. In the categories of different content it was found that not all children in the class achieved equal results. But they all advanced. Noting that this educational performance improves students' learning, however, it is an additional practice of pedagogical work, which faces challenges and needs an organization to make it effective. In addition, it is not enough to have G.I. one must also make the activity happen and make it contributory. The student has a crucial role in improving their learning, it takes effort and dedication. It is each participant who modifies and enriches the performance of the Interactive Group in the classroom.